Review : Animal Models Of Diabetes Mellitus : Pathology And Mechanism Of Some Diabetogenics - AGUNG ENDRO NUGROHO (Society for Indonesian Biodiversity, 2006)
Animal models of diabetes mellitus were made and used in laboratorium according to the pathology of diabetic patient and its complications. Animal models of diabetes mellitus were designed by two methods: induced method such as pancreatectomy, chemicals (diabetogenic), viruses, and spontaneous method such BB (bio breeding) rats and NOD (non-obese diabetic) mice. The techniques of animal models of diabetes mellitus frequently used in the research were usage of diabetogenic such as alloxan and streptozotocin. Alloxan and its reduction metabolite (dialuric acid) establish a redox cycle and form superoxide radicals, and they undergo dismutation to hydrogen peroxide. By Fenton reaction, the formation of reactive hydroxyl radicals was stimulated. These radicals with high concentration of cytosolic calcium cause rapid destruction of Î² cells. Besides, streptozotocin enters the Î² cell through a glucose transporter (GLUT2), and stimulates superoxide radicals, hydrogen peroxide and hydroxyl radicals which in turn causes rapid destruction of Î² cells. Streptozotocin also releases toxic amounts of nitric oxide that inhibits aconitase activity and contributes in DNA damage.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: animal models, diabetes mellitus, alloxan, streptozotocin.